Analisis Kadar Air Terhadap Kualitas Karbon Aktif Dari Cangkang Buah Karet - Rudea Faddhisrah Syahbana; Aryo Sasmita; Edward HS (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Activated carbon is a material containing amorphous carbon which has an internal surface so that it has high adsorption. Activated carbon has the potential to be used as an adsorbent. This study aims to utilize rubber fruit shells as raw material for making activated carbon. Activated carbon was prepared by carbonization process at 500°C for 1 hours using 10% H3PO4 activator and sieving with a filter size of 200 mesh. The activated carbon product is then tested using proximate analysis. The results of the proximate analysis show that activated carbon has met SNI 06-3730-1995 with a moisture content of 7,6%. Keywords: Activated carbon, Activation, Adsorption, Emission gas, Rubber fruit shells